Predicting future athletic performance in young female road cyclists based on aerobic fitness and hematological variables - Sitkowski, D.; Malczewska-Lenczowska, J.; Zdanowicz, R.; Starczewski, M.; Pokrywka, A.; Zmijewski, P.; Faiss, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed to determine whether the initial levels of aerobic fitness and hematological variables in young female road cyclists are related to their athletic performance development during their careers.